2016
DOI: 10.1111/scs.12404
|View full text |Cite
|
Sign up to set email alerts
|

Areas for quality improvements in heart failure care: quality of care from the patient's perspective

Abstract: Important areas for improvement in the quality of care for patients with heart failure in an outpatient setting were identified, such as symptom alleviation, information, participation and access to care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…He suggests the need of new collaboration models that include healthcare professionals, patients and their families to reduce fragmentation and enhance continuity of care. A Swedish study showed that there is a great potential for improvement regarding access to care and treatment over time in patients with HF [26].…”
Section: Introductionmentioning
confidence: 99%
“…He suggests the need of new collaboration models that include healthcare professionals, patients and their families to reduce fragmentation and enhance continuity of care. A Swedish study showed that there is a great potential for improvement regarding access to care and treatment over time in patients with HF [26].…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature indicates rates of cachexia among Brazilians hospitalized with HF of up to 48.1% and 61.8% have malnutrition (Tinoco et al, 2021). From the patients’ perspective, effective treatment for loss of appetite is an area that requires quality improvement in HF care (Ängerud et al, 2017) and in the care delivered to older adults in general who are hospitalized (Brunner et al, 2022). This is the first study that systematically assessed the appetite of patients with HF in Brazil and the second in the world, to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…This study, presents that nurses experience access and flexibility in the care contacts as a basic prerequisite for continuity of care in patients with HF. Other studies in this area have highlighted access to care as an aspect of quality of health care that needs to be improved (Ängerud et al, 2017, 2018; Browne et al, 2014). In this study, the nurses stated that access to multidisciplinary teams and built‐in flexibility in planning visits were both essential to continuity of care for patients with HF.…”
Section: Discussionmentioning
confidence: 99%